The Effectiveness of Biorafia in Reducing Total Suspended Solid Content in the River Sail Water - Fradillah.S, Nailul; Budijono, Budijono; M. Hasbi, M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractSail River is one of the Siak watersheds which has high TSS levels. This study aims to determine the decrease in TSS levels using the different density of biorafia (plastic rope that functions as a filter). This research was conducted on the Sail River, from March to April 2019. The method used was CRD with 3 different biorafia densities: P1 (low density), P2 (medium density) and P3 (high density), with 3 replications. Sampling is done before passing the biorafia (inlet) and after passing through the biorafia (outlet). The highest reduction in TSS levels was found at moderate density (190 mg / L) with a decrease in effectiveness (EP) of 96,9%. The density of different biorafia does not significantly influence the decrease in TSS levels in the Sail River water. Keywords : Biocord, Biorafia, Suspended Solid and Bacteria